Effects of moisture content and temperature on storage of Metarhizium flavoride conidia - Moore, D.; Douro-Kpindou, O.K.; Jenkins, N.E.; Lomer,C.J. (Informa UK Limited, 1996)
The effects of moisture content and temperature on the medium-term (3-4 months) storage of conidia of Metarhizium flavoviride were investigated. Conidia harvested after 24 days of culturing on rice showed greater tolerance to long storage than conidia from 12-day cultures. The moistut-e content of the conidia was of greatest importance; at harvest from the culture. conidial moisture contents could be > 40%, while the optimal moisture content for storage was found to be 4-5%. Dried conidia stored in oil benefited from the addition of dried silica gel, as did conidia stored as powder. A range of mineral oils proved satisfactory for storage, and when dried silica gel was added to suspensions, germination levels were 79.8% after 105 days at 28-32°C. Dried conidia stored in oil maintained germination levels of up to 96 and 85% after 80 days at IO-14°C and 28-.UoC respectively. Dried conidia stored as powder retained germination levels of 95% at JO-I4°C. but only up to 27% at 28-32°C. In another experiment, dried conidia maintained greater than 90% germination over 128 days, with or without silica gel at JO-14°C or 15- 18°C.